A review of the critical role of vitamin D axis on the immune system - Gholamreza Daryabor; Nasser Gholijani; Fatemeh Rezaei Kahmini (Elsevier, 2023)
In recent years, the physiological and molecular functions of vitamin D (Vit-D) have been deeply investigated. At first, Vit-D was considered a regulator of mineral and skeletal homeostasis. However, due to the extensive-expression pattern of Vit-D receptor (VDR) in almost every non-skeletal cell, Vit-D is considered mainly a multifunctional agent with broad effects on various tissues, notably the immune system. The expression of VDR in immune cells such as dendritic cells, monocyte/macrophage, neutrophils, B cells and T cells has been well demonstrated. Besides, such immune cells are capable of metabolizing the active form of Vit-D which means that it can module the immune system in both paracrine and autocrine manners. Vit-D binding protein (DBP), that regulates the levels and homeostasis of Vit-D, is another key molecule capable of modulating the immune system. Recent studies indicate that dysregulation of Vit-D axis, variations in the DBP and VDR genes, and Vit-D levels might be risk factors for the development of autoimmune disease. Here, the current evidence regarding the role of Vit-D axis on the immune system, as well as its role in the development of autoimmune disease will be clarified. Further insight will be given to those studies that investigated the association between single nucleotide polymorphisms of DBP and VDR genes with autoimmune disease susceptibility.